Joint ESPGHAN/NASPGHAN Guidelines for the Management of Helicobacter pylori in Children and Adolescents (Update 2016). Issue 6 (June 2017) - Jones, Nicola L.; Koletzko, Sibylle; Goodman, Karen; Bontems, Patrick; Cadranel, Samy; Casswall, Thomas; Czinn, Steve; Gold, Benjamin D.; Guarner, Jeannette; Elitsur, Yoram; Homan, Matjaž; Kalach, Nicolas; et al.
ABSTRACT: Background: Because of the changing epidemiology of Helicobacter pylori infection and low efficacy of currently recommended therapies, an update of the European Society for Paediatric Gastroenterology Hepatology and Nutrition/North American Society for Pediatric Gastroenterology, Hepatology and Nutrition recommendations for the diagnosis and management of H pylori infection in children and adolescents is required. Methods: A systematic review of the literature (time period: 2009–2014) was performed. Representatives of both societies evaluated the quality of evidence using GRADE (Grading of Recommendation Assessment, Development, and Evaluation) to formulate recommendations, which were voted upon and finalized using a Delphi process and face-to-face meeting. Results: The consensus group recommended that invasive diagnostic testing for H pylori be performed only when treatment will be offered if tests are positive. To reach the aim of a 90% eradication rate with initial therapy, antibiotics should be tailored according to susceptibility testing. Therapy should be administered for 14 days, emphasizing strict adherence. Clarithromycin-containing regimens should be restricted to children infected with susceptible strains. When antibiotic susceptibility profiles are not known, high-dose triple therapy with proton pump inhibitor, amoxicillin, and metronidazole for 14 days or bismuth-based quadruple therapy is recommended. Success of therapy should be monitored after 4 to 8 weeks by reliable noninvasive tests. Conclusions: The primary goal of clinical investigation is to identify the cause of upper gastrointestinal symptoms rather than H pylori infection. Therefore, we recommend against a test and treat strategy. Decreasing eradication rates with previously recommended treatments call for changes to first-line therapies and broader availability of culture or molecular-based testing to tailor treatment to the individual child.